Pengaruh Media PhET Simulation Terhadap Hasil Belajar Fisika Siswa Kelas 12 MIA/SMAIT Yapira Raudhatut Tauhid - Enda Maryati (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
This research aims to determine the effect of PhET simulation on student learning outcomes in direct current electricity material at SMAIT Yapira Raudhatut Tauhid. The research method used in this research is an experimental method with a quantitative approach. The population in this study was class 12 students at SMAIT Yapira Raudhatut Tauhid with the sample size being class 12-3 with a total of 30 students, as the control class and class 12-2 with a total of 30 students as the experimental class. The results of the research show that there is a significant influence of the PhET Simulation media on the physics learning outcomes of class 12 students at MIA/SMAIT Yapira Raudhatut Tauhid. This can be proven by obtaining a value of t.count > t.table = 4.827 > 2.048.